Patterns and Disparities in Research Funding in Spain: An analysis of Knowledge Generation Projects (2020-2023) - Moreno-Delgado, Alicia; Merino-Arribas, Adoración; Repiso, Rafael (Revista General de Información y Documentación, 2025)
Public research funding plays a crucial role in scientific development, shaping the priorities and competitiveness of universities and research institutions. This study presents a bibliometric analysis of research project funding under the Knowledge Generation Projects program (2020–2023), examining trends, distribution, and disparities across institutions, disciplines, and regions. Data from 25,501 project applications were analyzed, revealing that 12,600 projects received funding, while 12,901 were rejected. The study highlights significant differences in funding success rates among universities, public research organizations (OPIs), and the Spanish National Research Council (CSIC). Results indicate that CSIC leads in both success rate (67.43%) and funding per project, while private universities show the lowest success rate (30.14%) and receive marginal funding. The analysis also uncovers disparities among scientific disciplines, with physical sciences, mathematics, and biomedicine receiving higher success rates and funding per project, whereas humanities and social sciences exhibit lower success rates. Geographically, Catalonia and Madrid emerge as the primary beneficiaries, while regions like La Rioja, Extremadura, and the Canary Islands receive less funding per capita. These findings suggest a persistent concentration of resources in well-established institutions and regions, raising concerns about equity in research funding distribution. The study contributes to the debate on public funding policies by providing a comprehensive overview of trends, challenges, and potential areas for improvement in Spain’s competitive research funding system.
Keywords: Public funding; universities; research projects; scientific research; Spain